2021
DOI: 10.1021/acs.jmedchem.1c00029
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an Orally Efficacious Positive Allosteric Modulator of the Glucagon-like Peptide-1 Receptor

Abstract: The identification of LSN3318839, a positive allosteric modulator of the glucagon-like peptide-1 receptor (GLP-1R), is described. LSN3318839 increases the potency and efficacy of the weak metabolite GLP-1(9-36)NH 2 to become a full agonist at the GLP-1R and modestly potentiates the activity of the highly potent full-length ligand, GLP-1(7-36)NH 2 . LSN3318839 preferentially enhances G protein-coupled signaling by the GLP-1R over β-arrestin recruitment.Ex vivo experiments show that the combination of GLP-1(9-36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Allosteric modulation by PAMs that bind anywhere distinct from the orthosteric site of endogenous ligands and enhance the activity of agonists in an uncompetitive way is an alternative approach to peptide therapy 19 22 . Previous studies showed that several PAMs of GLP-1R, such as the most characterized electrophilic chemotype compound BETP 23 , 24 and the substituted quinoxaline compound 2 (6,7-dichloro-3-methanesulfonyl-2-tert-butylamino-quinoxaline) 25 , 26 , were able to initiate or promote receptor activation 9 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Allosteric modulation by PAMs that bind anywhere distinct from the orthosteric site of endogenous ligands and enhance the activity of agonists in an uncompetitive way is an alternative approach to peptide therapy 19 22 . Previous studies showed that several PAMs of GLP-1R, such as the most characterized electrophilic chemotype compound BETP 23 , 24 and the substituted quinoxaline compound 2 (6,7-dichloro-3-methanesulfonyl-2-tert-butylamino-quinoxaline) 25 , 26 , were able to initiate or promote receptor activation 9 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Drugs that target a GLP-1R allosteric site may improve receptor specificity, thereby reducing side effects. Most of the allosteric modulators of the GLP-1R that have been described (Figure ) display suboptimal potency and/or pharmacokinetics. Recently, a program toward optimization of LSN3160440 has succeeded in the discovery of structurally related LSN3318839 as an orally efficacious GLP-1 modulator . Herein, we report the discovery of the small molecule V-0219 (compound 9 ), a very potent PAM of the GLP-1R that doubles insulin secretion at nanomolar concentrations and shows oral activity in rodent models of food intake and glucose handling.…”
Section: Introductionmentioning
confidence: 82%
“… 20 25 Recently, a program toward optimization of LSN3160440 has succeeded in the discovery of structurally related LSN3318839 as an orally efficacious GLP-1 modulator. 26 Herein, we report the discovery of the small molecule V-0219 (compound 9 ), a very potent PAM of the GLP-1R that doubles insulin secretion at nanomolar concentrations and shows oral activity in rodent models of food intake and glucose handling.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, small molecules’ positive allosteric modulators (PAMs) of the GLP-1 receptor have been characterized [ 64 , 65 , 66 ]. These molecules would enhance receptor signaling when the endogenous ligand is present, thereby providing an opportunity to enhance the normal GLP-1 response selectively [ 64 ] Some of these PAMS interact with the less active form of GLP-1, potentiating the activity of GLP-1(9−36) by interacting with both the peptide and the receptor [ 64 , 65 , 66 ].…”
Section: Glucagon-like Peptide 1 and The Glp-1 Receptor Agonistmentioning
confidence: 99%